Analysis of Inter-language Syllabification of English by Pakistani Hindko- English Speakers - Hussain Mir, Shahid; Afsar, Ayaz (Pakistan Languages and Humanities Review, 2022)
Hindko is an Indo-Aryan language spoken in the Hazara and Azad Kashmir regions. The current research aims to analyze the interlanguage syllabification of English by Pakistani-Hindko speakers of English under optimality theory (Prince & Smolensky, 1993). The current study argues that Hindko English speakers syllabify the English syllables influenced by L1. The study uses the elicitation method to collect the data. The syllabification was analyzed under the optimality framework. The current study analyses the markedness and alignment constraints that predict the syllabification of stop clusters at word medial position by Hindko English speakers. The study finds that Hindko-English syllabification can be correctly predicted through parsing and phonological processes like epenthesis and ambisyllabicity. Moreover, the study reveals that in Hindko, these processes are conditioned by markedness and faithfulness constraints. In addition, the study concludes that in Hindko-English, cyclic CON, EVAL and local encoding are the best ways to study the phonological processes. The study recommends a further, in-depth investigation of phonological processes like epenthesis based on spectrographic analysis.